Efficacy and Safety of Vaginal Laser Therapy for Stress Urinary Incontinence: Systematic Review of Randomized Controlled Trials - Shiekedien, Elsadig Eltahir Khalid; Ahmed A Farhan, Dania; Jarah, Rawan Abdullah A; Aljammaz, Samaher Sulaiman F; Alatawi, Wafa Eid M; Alghbban, Raghad Talal M; Almasoudi, Bdour Awad S; Alomrani, Rawan Salem M; Aljohany, Melad Ahmed G; Alhawiti, Yasmeen Saleem (Saudi Medical Horizons Journal, 2025)
Vaginal laser therapy has emerged as a popular, minimally invasive treatment for stress urinary incontinence (SUI), proposed to work through thermal tissue remodeling. However, evidence from randomized controlled trials (RCTs) is conflicting, creating uncertainty for its clinical use. To systematically review and synthesize evidence from RCTs on the efficacy and safety of vaginal laser therapy for the treatment of pure SUI in women. A systematic review was conducted following PRISMA guidelines. A comprehensive search of PubMed/MEDLINE, Web of Science, SCOPUS, and Cochrane Central was performed. Only RCTs comparing vaginal laser (Er:YAG or CO2) to sham procedures, pelvic floor muscle training (PFMT), or other controls in women with SUI were included. Six RCTs with a total of 466 participants were included. The findings were highly inconsistent. Two sham-controlled RCTs reported significant improvement in the laser group for objective cure (59% vs. 36% sham) and quality of life. In contrast, three other sham-controlled RCTs found no significant difference between laser and sham on primary outcomes, with one reporting a subjective cure rate of less than 2% in both groups. One trial found laser to be non-inferior to PFMT at 4 months, but both interventions had low long-term success, with most patients seeking alternative treatments within two years. Heterogeneity was high regarding laser parameters, outcome measures, and patient populations. The procedure was consistently safe, with only minor, transient adverse events reported. Given the high cost and unproven efficacy, vaginal laser should not replace established SUI treatments. It should be considered investigational and used only in the context of further large, well-designed RCTs with long-term follow-up.